Primary renal squamous cell carcinoma in a non-functioning kidney with nephrolithiasis: A case report (Indian Journal of Case Reports, 2020)
Primary squamous cell carcinoma (SCC) of renal pelvis is a rare neoplasm. A 50-year-old female presented with a history of chronic dull aching pain in left flank region and burning micturition for 8 months. Workup showed multiple calculi in non-functioning, hydronephrotic left kidney. Histopathological examination of nephrectomy specimen revealed SCC of renal pelvis; although, there was no obvious growth. The case report highlights the fact that SCC should be suspected in a patient with renal mass in a non-functioning kidney following long-standing nephrolithiasis.